Performance in place of war - Thompson, James; Hughes, Jenny, 1971-; Balfour, Michael, 1966- (Calcutta : Seagull Books, 2009)
'Performance in Place of War' is concerned with theatre in refugee camps, in war-affected villages, in towns under curfew, in cities under occupation. It presents theatre and performance that occurs literally at the moment bombs are falling, as well as during times of ceasefire and in the aftermaths of war
Includes bibliographical references (p. [319]-331) and index.
boek
Keywords: War and theater; Theater -- Social aspects